Update on diagnosis of Pneumocystis jirovecii pneumonia. - Teeranaipong, P. (Chulalongkorn Medical Journal, 2023)
Pneumocystis jirovecii pneumonia (PCP) is a common and life-threatening infection in immunocompromised patients. A timely diagnosis and early administration of proper treatment is essential to prevent acute respiratory failure which is associated with high motality. Since symptoms and signs of PCP are mostly nonspecific, detection of P. jirovecii or pneumocystis DNA in respiratory specimen is necessary for definite diagnosis of PCP. Many adjunct tests are warranted. Microscopic examinations by different staining methods are fundamental, but highly helpful, for diagnosis of PCP. In many cases especially PCP in non-HIV group, the fungal load might be lower than microscopic detection threshold. Meanwhile, several serologic markers ((1-3)-beta-D-glucan (BDG), lactate dehydrogenase (LDH), S-adenosylmethionine, major surface glycoprotein (MSG) antibody test) have been proposed with diversely reported sensitivity and specificity. Imaging studies such as chest X-ray (CXR), thoracic ultrasonography, high-resolution computed tomography (HRCT) have been studied for both diagnosis and help evaluation of disease burden. High sensitivity and specificity of advanced quantitative PCR are also very helpful but still the standard protocol to distinguish between infection and colonization is not well-developed and become a challenge. Recently, cultivation of Pneumocystis has been reported successful. This sheds light on further understanding of the biology and natural history of pneumocystosis and a better way to deal with.